A case series of mamushi bite and adverse effects of antiserum injection in several cases - Kondo, Makoto; Goto, Hiroyuki; Yamamoto, Shinya (International Journal of Advances in Medicine, 2016)
Eight cases of mamushi bite and associated adverse events, including serum sickness diseases, delayed response, and adverse effects of antivenom were reported at hospital from May to September 2015. Adverse effects were seen in cases 3, 6 and 7 during treatment for mamushi bite. The underlying causes for the high frequency and variety of adverse effects of mamushi antivenom, including adverse reactions and serum sickness disease, are still not fully elucidated. Mumashi antivenom can be a major contributing factor to reducing hospital stay duration. However, healthcare professionals should be aware of the potential adverse reactions to mamushi antivenom.